Anode active material precursor for lithium secondary battery, anode active material containing the same, and method for producing the same

A carbon-based negative electrode active material precursor with petroleum-based pitch and metal compound addresses high-temperature degradation issues, ensuring improved structural stability and rapid charging performance in lithium secondary batteries.

JP2025500374AActive Publication Date: 2025-01-09CLEANSOLUTION CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024537490
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-21
Filing Date
2022-12-06
Publication Date
2025-01-09
Estimated Expiration
2042-12-06

AI Technical Summary

Technical Problem

Existing carbon-based negative electrode active materials for lithium secondary batteries face issues with high-temperature performance degradation due to changes in electrode structure and internal pore volume during rolling, limiting high-temperature storage and cycling characteristics, and require improvements for rapid charging capabilities.

Method used

A negative electrode active material precursor is developed using a carbon-based material combined with a petroleum-based pitch, containing a metal compound, with specific particle size, purity, and pitch content to enhance hardness and electrical conductivity, followed by a controlled mixing and heat-treatment process.

Benefits of technology

The precursor results in a negative electrode active material with improved high-temperature performance and rapid charging capabilities, maintaining structural integrity and enhancing discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500374000001_ABST
    Figure 2025500374000001_ABST
Patent Text Reader

Abstract

The present embodiment relates to a negative electrode active material precursor, a negative electrode active material, and a manufacturing method thereof. The negative electrode active material precursor according to the embodiment includes a carbon-based material containing a metal compound and a petroleum-based pitch, and the petroleum-based pitch may include 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material, the softening point of the petroleum-based pitch may be 220 to 280° C., and the content of the metal compound may be 10 ppm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present embodiment relates to a secondary battery, and more particularly to a negative electrode active material for a lithium secondary battery, a manufacturing method thereof, and a lithium secondary battery including the same. [Background technology]

[0002] A lithium secondary battery generally comprises a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator, and an electrolyte, and is charged and discharged by the intercalation-decalation of lithium ions. The lithium secondary battery has the advantages of high energy density, large electromotive force, and high capacity, and is therefore used in a variety of fields.

[0003] In addition, it is an important issue to improve high-temperature performance such as high-temperature storage characteristics and high-temperature cycle characteristics in lithium secondary batteries. For example, if the total internal pore volume is high after applying a negative electrode active material to a current collector and rolling it, there is a high possibility that the high-temperature performance of the negative electrode will be reduced. Therefore, it is necessary to improve high-temperature characteristics when developing a negative electrode material for lithium secondary batteries, for example, fast-charging secondary batteries, by minimizing changes in the electrode structure and the total internal pore volume that occur during electrode rolling.

[0004] In addition, as technological development and demand for mobile devices increases, the demand for secondary batteries as an energy source is rapidly increasing. Among secondary batteries, lithium secondary batteries, which exhibit high energy density and working potential, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0005] In addition, as interest in environmental issues grows, interest is growing in electric vehicles and hybrid electric vehicles that can replace vehicles that use fossil fuels, such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and active research is being conducted into the use of lithium secondary batteries as a power source for electric vehicles and hybrid electric vehicles.

[0006] Recently, with the sudden rise of EVs, expectations for lithium secondary batteries are growing, and there is an increasing demand for improved fast charging characteristics while maintaining existing capacity. The role of negative electrode active materials, which are responsible for storing lithium ions during charging, is becoming increasingly important in improving fast charging.

[0007] As the negative electrode active material, a metallic lithium negative electrode active material, a carbon-based negative electrode active material, or silicon oxide (SiO x ) are used. Carbon-based negative electrode active materials show excellent capacity storage characteristics and efficiency. Carbon-based negative electrode active materials used as the negative electrodes of lithium secondary batteries have a potential close to that of lithium metal, so that there is little change in the crystal structure during the insertion and desorption process of ionic lithium. In addition, carbon-based negative electrode active materials enable sustained and repeated oxidation and reduction reactions at the electrode, enabling lithium secondary batteries to exhibit high capacity and excellent life.

[0008] Carbon-based negative electrode active materials are used in various forms, such as crystalline carbon-based materials such as natural graphite and artificial graphite, and amorphous carbon-based materials such as hard carbon and soft carbon. Among carbon-based negative electrode active materials, graphite-based negative electrode active materials are the most widely used because of their excellent reversibility and ability to improve the life characteristics of lithium secondary batteries. Graphite-based negative electrode active materials have a lower discharge voltage of -0.2V compared to lithium, so batteries using graphite-based active materials can exhibit a high discharge voltage of 3.6V, offering excellent advantages in terms of energy density for lithium secondary batteries.

[0009] The crystalline carbon material artificial graphite has a more stable crystal structure than natural graphite because the graphite crystal structure is created by applying high thermal energy of 2,700°C or more. The change in the crystal structure is small even with repeated charging and discharging of lithium ions, and artificial graphite has the advantage of having a lifespan that is two to three times longer than natural graphite. Soft carbon and hard carbon, which are amorphous carbon materials with an unstabilized crystal structure, have the property of allowing lithium ions to penetrate more smoothly, which increases the charging and discharging speed, and can be used for electrodes that require high-speed charging. Therefore, it is common to mix carbon materials in a certain ratio and use them, taking into account the lifespan and output characteristics of the lithium secondary battery to be used.

[0010] However, among graphite-based negative active materials, natural graphite has a problem of low hardness and requires a coating process to impart hardness, but the coating process has a problem of limiting the production of high-capacity batteries. Summary of the Invention [Problem to be solved by the invention]

[0011] The technical problem to be solved by the present invention is to provide a negative electrode active material precursor that ensures high hardness and electrical conductivity.

[0012] Another technical problem to be solved by the present invention is to provide a negative electrode active material having the above-mentioned advantages.

[0013] Another technical problem to be solved by the present invention is to provide a method for producing a negative electrode active material having the above advantages. [Means for solving the problem]

[0014] A negative electrode active material precursor according to an embodiment of the present invention includes a carbon-based material containing a metal compound and a petroleum-based pitch, the petroleum-based pitch may be included in an amount of 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material, the softening point of the petroleum-based pitch may be 220 to 280° C., and the content of the metal compound may be 10 ppm or more. In one embodiment, the carbon-based material may be at least one of natural graphite, softened carbon, hardened carbon, kish graphite, pyrolytic carbon, liquid crystalline pitch-based carbon fiber, mesophase graphite powder, carbon microspheres, liquid crystalline pitch, and coal-based coke.

[0015] In one embodiment, the carbon-based material may have a purity of 97% or more. In one embodiment, the carbon-based material may have an average particle size D50 of 13 to 17 μm.

[0016] In one embodiment, the petroleum-based pitch may have a beta resin content of 15 to 40%. In one embodiment, the petroleum-based pitch may have a residual mass of 50% or less when measured at a standard temperature of 400° C. In one embodiment, the metal compound may be a compound containing at least one metal element selected from Fe, Si, Ge, Sn, Pb, P, Sb, Bi, Al, Ga, In, Ti, Mn, Co, Ni, Cu, Zn, Ag, Mg, Sr, and Ba, or a mixture thereof.

[0017] According to another embodiment, the negative electrode active material may include a negative electrode active material precursor including a carbon-based material containing a metal compound and a petroleum-based pitch, the petroleum-based pitch being included in an amount of 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material, the softening point of the petroleum-based pitch being 220 to 280° C., and the content of the metal compound being 10 ppm or more. In one embodiment, the negative electrode active material may satisfy the following formula 1.

[0018] <Expression 1> ((Span2-Span1) / Span1)×100≦15% (In the above formula 1, Span1 is (D90-D10) / D50 of the negative electrode active material, Span2 is (D90-D10) / D50 of the negative electrode active material after a shear force test at 1,000 rpm, and D10, D50, and D90 respectively mean particle sizes corresponding to 10%, 50, and 90% of the cumulative volume from the smallest particle size.)

[0019] According to another embodiment, a method for manufacturing a negative electrode active material precursor includes: preparing a carbon-based material including 10 ppm or more of a metal compound; adjusting a particle size of the carbon-based material to 13 to 18 μm; adding 3 to 10 parts by weight of a petroleum-based binder pitch to the carbon-based material, based on 100 parts by weight of the carbon-based material; and mixing the carbon-based material and the petroleum-based binder pitch, wherein the softening point of the petroleum-based binder pitch may be 220 to 280° C.

[0020] In one embodiment, adjusting the particle size of the carbon-based material may include pulverizing the carbon-based material by at least one of physical impact and airflow impact. In one embodiment, mixing the carbon-based material and the petroleum-based binder pitch may be performed by applying a rotational shear force. Effect of the Invention

[0021] According to one embodiment of the present invention, by utilizing a precursor having high hardness, it is possible to provide an anode active material precursor for producing an anode material having high discharge capacity derived from natural graphite by utilizing a thin coating film, which exhibits high performance even when a low coating film is formed.

[0022] According to another embodiment of the present invention, there is provided an anode active material including an anode active material precursor having the above-mentioned advantages.

[0023] According to another embodiment of the present invention, a method for manufacturing a negative electrode active material having the above advantages can be provided. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a flow chart of a method for preparing a negative electrode active material precursor according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Terms such as first, second and third are used to describe various parts, components, regions, layers and / or sections, but are not limited thereto. These terms are used only to distinguish one part, component, region, layer or section from another part, component, region, layer or section. Thus, a first part, component, region, layer or section described below can be referred to as a second part, component, region, layer or section without departing from the scope of the present invention.

[0026] The terminology used herein is merely for the purpose of referring to particular embodiments and is not intended to limit the present invention. As used herein, the singular form includes the plural form unless the phrase clearly indicates otherwise. The term "comprising" as used herein embodies certain features, regions, integers, steps, operations, elements and / or components and does not exclude the presence or addition of other features, regions, integers, steps, operations, elements and / or components.

[0027] When an element is referred to as being "on" or "above" another element, this may be immediately on or above the other element, or there may be other elements in between. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.

[0028] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by a person having ordinary skill in the art to which the present invention belongs. Terms defined in commonly used dictionaries are additionally interpreted as having a meaning consistent with the relevant technical literature and the currently disclosed content, and are not interpreted in an ideal or very formal sense unless defined.

[0029] Hereinafter, embodiments of the present invention will be described in detail, however, they are presented by way of example only and are not intended to limit the present invention, which is defined only by the scope of the claims set forth below.

[0030] According to an embodiment of the present invention, a negative electrode active material precursor includes a carbon-based material containing a metal compound and a petroleum-based pitch. The negative electrode active material precursor is a base material for a negative electrode active material, and is required to have high electrochemical properties in order to be used in a secondary battery.

[0031] The carbon-based material may be various carbon-based materials such as low-crystalline carbon and high-crystalline carbon. The low-crystalline carbon may include at least one of soft carbon and hard carbon, and the high-crystalline carbon may include carbon-based materials such as natural graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesophase graphite powder (MGP), meso-carbon microbeads, mesophase pitches, and coal tar derived cokes, artificial graphite, graphitized carbon fiber, and resin sintered body. Specifically, the carbon-based material of the present invention may be natural graphite.

[0032] In an embodiment, the carbon-based material may have at least one of a flake shape, a sphere shape, and a lump shape. Specifically, the carbon-based material may be spherical natural graphite particles.

[0033] In one embodiment, the carbon-based material includes the metal compound, which may be, for example, a compound containing at least one metal element selected from the group consisting of Fe, Si, Ge, Sn, Pb, P, Sb, Bi, Al, Ga, In, Ti, Mn, Co, Ni, Cu, Zn, Ag, Mg, Sr, and Ba, or a mixture thereof, and may specifically include Fe.

[0034] In one embodiment, the carbon-based material may contain 10 ppm or more of the metal compound. When the metal compound is 10 ppm or more by weight, the material can be used as an anode material with an electrical conductivity of 150 s / cm or more. If the content is less than the range, the material is difficult to use as an anode material due to low electrical conductivity.

[0035] In one embodiment, the carbon-based material may have a purity of 97% or more. Specifically, the carbon-based material may have a fixed carbon content of 97% or more. If the purity of the carbon-based material is lower than this, there is a problem that performance is deteriorated due to impurities.

[0036] In one embodiment, the average particle diameter D50 of the carbon-based material may be in the range of 13 to 17 μm. The D50 refers to a particle diameter corresponding to 50% of the volume cumulative from the small particle diameter side. If the average particle diameter of the carbon-based material is outside the upper limit of the range, the base material becomes excessively large, and there is a limit to the strength retention due to the limit of the coverage of the binder pitch. If the average particle diameter of the carbon-based material is outside the lower limit of the range, the specific surface area becomes excessively high, and an excessive amount of binder pitch is required, resulting in a problem that a decrease in the capacity of the battery due to the excessive amount of binder pitch is unavoidable.

[0037] The petroleum pitch is included in an amount of 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material. Specifically, the petroleum pitch is included in an amount of 3 to 10 parts by weight based on the carbon-based material.

[0038] If the content of the petroleum-based pitch is outside the upper and lower limits of the range, when a negative electrode material is manufactured using a negative electrode active material precursor containing the petroleum-based pitch, there is a problem that the increase rate of the span value of the negative electrode material after a shear force test is excessively high with respect to the span value of the negative electrode material. The excessive increase rate of the span value causes problems such as excessive generation of fine powder, peeling of the coating layer, and separation of particles. Specifically, there is a problem that the adhesion between the coating material and the surface of the base material is reduced, thereby deteriorating the function as a negative electrode active material.

[0039] In one embodiment, the softening point of the petroleum pitch is in the range of 220 to 280° C. When the softening point is in the range, there is an advantage that the function as a negative electrode active material is excellent.

[0040] If the above range is not satisfied, the increase rate of the span value becomes too high, which may cause the coating layer to peel off and the particles to separate.

[0041] In one embodiment, the residual weight at 400° C. may be 50% or less based on the weight of the petroleum pitch. If the residual weight is more than 50%, there is a problem in that the insertion and desorption of lithium ions becomes difficult due to an increase in amorphous carbon structure during battery manufacturing, resulting in a decrease in battery efficiency.

[0042] In one embodiment, the petroleum pitch may have a beta resin content of 15 to 40 wt %. The beta resin may act as an adhesive when manufacturing the negative electrode material.

[0043] According to another embodiment of the present invention, the negative electrode active material is a negative electrode active material for a lithium secondary battery, which is produced by heat-treating the above-mentioned negative electrode active material precursor. The negative electrode active material of the present invention satisfies the following formula 1.

[0044] <Expression 1> ((Span2-Span1) / Span1)×100≦15% (In the above formula 1, Span1 is (D90-D10) / D50 of the negative electrode active material, Span2 is (D90-D10) / D50 of the negative electrode active material after a shear force test at 1,000 rpm, and D10, D50, and D90 respectively mean particle sizes corresponding to 10%, 50, and 90% of the cumulative volume from the smallest particle size.)

[0045] The Span1 may be a span value when the above-mentioned negative active material precursor is carbonized to produce a negative active material. The carbonization may be performed at a temperature range of, for example, 900° C. or higher. The Span2 may be a value obtained by measuring a change in span value after a shear force test is performed on the negative active material.

[0046] If the value of the formula 1 does not satisfy the above range, there is a problem that excessive fine powder is generated, which causes the coating layer to peel off and the particles to separate. Specifically, there is a problem that the adhesion between the coating material and the surface of the base material is reduced, which deteriorates the function as a negative electrode active material.

[0047] FIG. 1 is a flow chart of a method for preparing a negative electrode active material precursor according to one embodiment of the present invention.

[0048] 1, the method includes the steps of preparing a carbon-based material including a metal compound (S100), adjusting the particle size of the carbon-based material (S200), adding a petroleum-based binder pitch to the carbon-based material (S300), and mixing the carbon-based material and the petroleum-based binder pitch (S400). Detailed descriptions of the carbon-based material, the petroleum-based binder pitch, and the metal compound may be referred to within the scope not inconsistent with the descriptions of the negative electrode active material precursor and the negative electrode active material described above.

[0049] The step of preparing a carbon-based material containing a metal compound (S100) may prepare a carbon-based material containing 10 ppm or more of the metal compound. By containing 10 ppm or more of the metal compound, the carbon-based material can be used as a negative electrode material with excellent electrical conductivity.

[0050] The step of adjusting the particle size of the carbon-based material (S200) may adjust the particle size of the carbon-based material to 13 to 18 μm. The step of adjusting the particle size of the carbon-based material (S200) may be controlled by physical impact. The physical impact may be achieved by using equipment that utilizes physical impact, such as a jet mill, an air classifier mill, or a roller mill. The jet mill directly pulverizes particles using collision between particles, the air classifier pulverizes particles using airflow, and the roller mill pulverizes particles by feeding, pressing, and pulverizing particles between two or more rollers rotating in opposite directions.

[0051] The step of adding the petroleum-based binder pitch to the carbon-based material (S300) may include adding 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material. By satisfying this range, it is possible to prevent the increase rate of the span value from becoming excessively large.

[0052] The step of mixing the carbon-based material and the petroleum-based binder pitch (S400) may utilize a mixing method such as a dry method or a wet method. Specifically, the step of mixing the carbon-based material and the petroleum-based binder pitch (S400) may be performed by at least one of an airflow method, a granulation spheronization method, and a mechanical milling method.

[0053] The method using an airflow may involve mixing by friction between a wall surface and the negative active material precursor caused by an airflow using centrifugal force. The granulation and spheronization method may include a dry method in which pulverized particles are treated with a milling method such as a blade mill, a multipurpose mixer pulverizer, or a combination thereof, and a wet method using spray drying, in which pulverized particles are treated with a milling method such as a blade mill, a multipurpose mixer pulverizer, or a combination thereof, in which the carbon-based material and the petroleum-based binder pitch are milled and mixed in the mechanical milling method, in which two or more rollers rotate while causing friction in a vertical direction.

[0054] The step of mixing the carbon-based material and the petroleum-based binder pitch (S400) may include a step of forming a coating layer. The coating layer may be formed by mixing the carbon-based material and the petroleum-based binder pitch, and coating the petroleum-based binder pitch on a surface of the carbon-based material.

[0055] In one embodiment, after the negative active material precursor and the coating material are mixed to form the coating layer, a shear and / or compression force may be applied to the negative active material precursor so that the coating material is disposed on the surface of the negative active material precursor.

[0056] According to another embodiment of the present invention, a lithium secondary battery may include a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a separator and an electrolyte disposed between the positive electrode and the negative electrode.

[0057] The positive electrode is LiCoO2, LiNiO2, LiNix Mn y O2, Li 1+z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z The positive electrode may be any one of the group consisting of LiFePO4, LiCoO2, NCM811, and NCM622, where x is 0.3 to 0.8, y is 0.1 to 0.45, and z is independently 0 to 0.2. More specifically, the positive electrode may be LiFePO4, LiCoO2, NCM811, and NCM622.

[0058] The negative electrode may be made of the negative active material precursor, the negative active material, or a negative active material prepared using a negative active material precursor prepared by a method for preparing a negative active material precursor.

[0059] The separation membrane may be a conventional porous polymer film used as a separator, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / propylene copolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in combination. Alternatively, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used, but these examples are not limiting.

[0060] In the electrolytic solution, the lithium salt that can be contained as the electrolyte can be any lithium salt that is commonly used as an electrolyte for lithium secondary batteries, without any limitation. For example, the anion of the lithium salt can be F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4- , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - It may be any one selected from the group consisting of:

[0061] In the electrolyte, the organic solvent may be any organic solvent commonly used in electrolytes for lithium secondary batteries without any limitation. Representative examples include any one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, gamma-butyrolactone, propylene sulfite, and tetrahydrofuran, or a mixture of two or more of these.

[0062] The lithium secondary battery may be disposed in a battery case, and the battery case may be any one of a cylindrical type using a can, a square type, a pouch type, and a coin type, as non-limiting examples. EXAMPLES

[0063] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may, however, be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.

[0064] <Negative electrode active material precursor> In the following examples and comparative examples, the electrical conductivity of the anode material is shown according to the content of iron (Fe) particles based on natural graphite spheroid particles, D50 of 16 μm, and density of 1.8 g / cc at 25° C. Specifically, the content of the iron particles was measured using ICP (Inductively Coupled Plasma).

[0065] [Table 1]

[0066] From Table 1, it can be seen that when the iron (Fe) content is 10 ppm or more, the electrical conductivity of the negative electrode material is 150 s / cm or more.

[0067] <Negative electrode active material> As shown in Table 2 below, petroleum pitch or coal pitch was mixed based on the negative active material precursor of Example 1 in Table 1, and then mixed by running the mixture in an idle state. The mixed material was then carbonized at 1,000°C for 1 hour to prepare a negative active material. A shear force test at 1,000 rpm was performed to measure the span change. The span is calculated as (D90-D10) / D50.

[0068] [Table 2]

[0069] From Table 2, it can be seen that the span value increases significantly when coal-based pitch is used. The increase in the span value means that a lot of fine powder is generated, and the generation of fine powder means that the coating layer is peeled off, the particles are separated, and the fine powder is generated due to low adhesion between the coating material and the base material surface. As a result, there is a problem that the functionality as a negative electrode active material is reduced due to low adhesion between the coating material and the base material surface.

[0070] Referring again to Table 2, when petroleum pitch is used, when the pitch content is 2 and 11%, the increase rate of the span value is 15% or more, which causes a problem of reduced functionality as a negative electrode active material.

[0071] Referring to Table 3 below, petroleum pitch or coal pitch was mixed at 5% extrapolation based on the negative active material precursor of Example 1 in Table 1, and then mixed by running the mixture in an idle state. The mixed material was then carbonized at 1,000°C for 1 hour to prepare a negative active material. The span change was measured by a shear force test at 1,000 rpm. Here, the span means the (D90-D10) / D50 value.

[0072] [Table 3]

[0073] From Table 3, it can be seen that the coal-based pitch has a large change rate of the span value regardless of the softening point. This confirms that the coal-based pitch is exfoliated during battery manufacturing.

[0074] Referring again to Table 3, it can be seen that in the case of petroleum-based pitch, the span increase rate is 15% or less only in Examples 2 to 4, which have a softening point greater than 210 and less than 280. Comparative Examples 1 and 5 use petroleum-based pitch as a base, but have softening points outside the range of the present invention, resulting in a span increase rate of more than 15%, and severe peeling during battery manufacturing.

[0075] <Electrochemical evaluation of lithium secondary batteries> In Table 4 below, the D50 of spherical natural graphite is 14 μm, the type of pitch is petroleum-based pitch, the softening point is 250° C., the pitch content is 6%, and the results of thermogravimetric analysis (TGA) of the pitch are shown based on the weight and the residual weight at 400° C. when two types of pitch, specifically, coal-based and petroleum-based pitches, are used.

[0076] Based on the examples and comparative examples shown in Table 4 below, electrochemical evaluation was carried out through the following process.

[0077] 97% by weight of the prepared negative active material, 2% by weight of binder containing carboxymethyl cellulose and styrene butadiene rubber, and 1% by weight of Super P conductive material were mixed in distilled water solvent to prepare a negative active material slurry. The negative active material slurry was applied to a copper (Cu) current collector and then vacuum dried in a vacuum oven at 100°C for 12 hours to prepare a negative electrode.

[0078] After vacuum drying, the electrode density of the negative electrode was adjusted to 1.5 to 1.7 g / cc. When manufacturing the slurry, the negative electrode material is included as one component, and a series of processes such as copper (Cu) coating are applied in the same way.

[0079] The negative electrode prepared by the above method and lithium metal (Li-Metal) were used as a counter electrode, and the electrolyte was a 1:1 volume ratio mixed solvent of ethylene carbonate (EC):dimethyl carbonate (DMC) in which 1 mol of LiPF6 was dissolved.

[0080] Using the above components, a 2032 coin cell type half coin cell was manufactured by a conventional manufacturing method.

[0081] [Table 4]

[0082] As seen from Table 4, it was found that when the remaining weight exceeds 50%, the efficiency of the battery decreases. This is because when the remaining weight is 50% or more, there is a problem in that the insertion and desorption of lithium ions is adversely affected due to an increase in the amorphous carbon structure.

[0083] The present invention is not limited to the above-mentioned embodiments, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains should understand that the present invention can be embodied in other specific forms without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and not limiting.

Claims

1. Carbon-based materials containing metal compounds and petroleum-based pitches, The petroleum pitch is contained in an amount of 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material, The softening point of the petroleum pitch is 220 to 280° C. The content of the metal compound is 10 ppm or more.

2. 2. The negative electrode active material precursor of claim 1, wherein the carbon-based material is at least one of natural graphite, softened carbon, hardened carbon, kish graphite, pyrolytic carbon, liquid crystal pitch-based carbon fiber, mesophase graphite powder, carbon microspheres, liquid crystal pitch, and coal-based coke.

3. The negative electrode active material precursor according to claim 1 , wherein the carbon-based material has a purity of 97% or more.

4. The negative electrode active material precursor of claim 1 , wherein the carbon-based material has an average particle size D50 of 13 to 17 μm.

5. 2. The negative electrode active material precursor of claim 1, wherein the petroleum pitch has a beta resin content of 15 to 40%.

6. The negative electrode active material precursor according to claim 1 , wherein the petroleum pitch has a residual mass of 50% or less when measured at a standard temperature of 400° C.

7. 2. The negative electrode active material precursor according to claim 1, wherein the metal compound is a compound containing at least one metal element selected from the group consisting of Fe, Si, Ge, Sn, Pb, P, Sb, Bi, Al, Ga, In, Ti, Mn, Co, Ni, Cu, Zn, Ag, Mg, Sr, and Ba, or a mixture thereof.

8. Carbon-based materials containing metal compounds and petroleum-based pitches, The petroleum pitch is contained in an amount of 3 to 10 parts by weight based on 100 parts by weight of the carbon-based material, The softening point of the petroleum pitch is 220 to 280° C. The content of the metal compound in the negative electrode active material precursor is 10 ppm or more.

9. The negative electrode active material according to claim 8 , which satisfies the following formula 1: <Formula 1> ((Span 2 -Span 1 ) / Span 1 )×100≦15% (In the above formula 1, Span 1 is the negative electrode active material's (D90-D10) / D50, and Span 2 is (D90-D10) / D50 after a shear force test of the negative electrode active material at 1,000 rpm, where D10, D50, and D90 mean particle sizes corresponding to 10%, 50%, and 90% of the cumulative volume from the smaller particle size, respectively.

10. Providing a carbon-based material containing 10 ppm or more of a metal compound; adjusting the particle size of the carbon-based material to 13 to 18 μm; adding 3 to 10 parts by weight of petroleum-based binder pitch to the carbon-based material based on 100 parts by weight of the carbon-based material; mixing the carbon-based material and the petroleum-based binder pitch; The softening point of the petroleum-based binder pitch is 220 to 280° C.

11. The method of claim 10, wherein the step of adjusting the particle size of the carbon-based material comprises a step of pulverizing the carbon-based material by at least one of physical impact and airflow impact.

12. The method for manufacturing a negative electrode active material precursor according to claim 10 , wherein the step of mixing the carbon-based material and the petroleum-based binder pitch is performed by applying a rotational shear force.

Citation Information

Patent Citations

  • High-density lithium ion battery anode material, and preparation method thereof

    CN108933240A

  • Nonaqueous electrolyte secondary battery

    JP2004265754A

  • Non-aqueous system secondary battery and its charging method

    JP2005285633A